ANALISIS PEMETAAN KONDISI TAMAN BACAAN MASYARAKAT (TBM) DI KOTA PEKANBARU - Fadilah Sari; Nining Sudiar; Vita Amelia (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2023)
The conditions of libraries in urban areas and universities are very different from the conditions in the Community Reading Gardens (TBM) which are currently also developing and increasing in Pekanbaru City, however amid the development of  TBM in Pekanbaru City there are still many TBM that do not yet have library collection standards, facilities and infrastructure standards, personnel standards, organizational standards, and management standards. Of the 36 Community Reading Gardens (TBMs) in Pekanbaru City, it is not yet clearly known what the condition is, both the condition of the collection and the condition of the infrastructure. So it is necessary to conduct further research related to the condition of the TBM in Pekanbaru City. This research used descriptive qualitative method. Data collection was done by observation, interview and documentation. Based on the results and discussion, it is found that only 11 TBMs are active with the dominant condition of TBMs already having a vision, mission and purpose of its establishment, judging from the target of its establishment, the average TBM has not determined who is the target of the establishment of TBMs. While in terms of human resources, the average TBM already has more than 3 administrators. Overall TBMs have provided reading services and on average TBMs have provided lending services. In terms of facilities, there are still minimal TBMs that provide decent facilities for their users. Activity programs provided by TBMs vary such as reading, drawing, coloring, book review and others. While promotional activities, the average TBM already has a social media account as a promotional tool. And in terms of cooperation, all TBMs have collaborated with organizations, communities, government agencies, and others.